Martial masculinities : Experiencing and imagining the military in the long nineteenth century - Begiato, Joanne; Barry, Anna Maria; Brown, Michael (Cultural history of modern war., 2019)
This collection explores the role of martial masculinities in shaping nineteenth-century British culture and society in a period framed by two of the greatest wars the world had ever known. It offers a fresh, interdisciplinary perspective on an emerging field of study and draws on historical, literary, visual and musical sources to demonstrate the centrality of the military and its masculine dimensions in the shaping of Victorian and Edwardian personal and national identities. Focusing on both the experience of military service and its imaginative forms, it examines such topics as bodies and habits, families and domesticity, heroism and chivalry, religion and militarism, and youth and fantasy. This collection will be required reading for anyone interested in the cultures of war and masculinity in the long nineteenth century.